Analysis of Cotton Fiber Kip Packaging Materials - Salimov, О.; Yuldosheva, О.; Salimov, А. (European Journal of Life Safety and Stability (2660-9630), 2021)
The article provides information about the packaging materials used in ginneries. The properties of various packing materials for cotton fiber bales have been studied.